ANALISIS PERILAKU INDEKS KEKERINGAN DI WILAYAH RENTAN KEBAKARAN, SUMATRA SELATANBEHAVIOR ANALYSIS OF DROUGHT INDEX IN FIRE-PRONE REGION OF SOUTH SUMATRA - Muh Taufik (Agromet, 2010)
Climate dynamics has a vital role in changing upper soil moisture that influences drought period and occurence especially for fire-prone region in South Sumatra Indonesia. Drought occurrence causes abundant dry fuel being available at peat forest ecosystem that might rise of fire risk and danger in the region. Using daily maximum air temperature and rainfall data for period of 1984-2009, we calculated daily Keetch-Byram drought index (KBDI) as an index for assessing fire danger potential. The index was gropued into three categories comprising low, moderate, and high fire danger levels.  Temporally, we found that fire danger level at the study area site are able to be grouped as follows: period of December to April was categorized low, period of July to October as high, and the remaining months as moderate. El Nino event had a severe influence on the severity and the duration of high KBDI that occurred until the end of November which normally a rainy season. Other finding is that there was a significant change (α=5%) on the rise of annual high KBDI frequency and average KBDI for period of 1984-2009, conversely frequency of rainy days decreased significantly. Information about when KBDI level reach high fire danger is of important for forest fire mangament in the region.Climate dynamics has a vital role in changing upper soil moisture that influences drought period and occurence especially for fire-prone region in South Sumatra Indonesia. Drought occurrence causes abundant dry fuel being available at peat forest ecosystem that might rise of fire risk and danger in the region. Using daily maximum air temperature and rainfall data for period of 1984-2009, we calculated daily Keetch-Byram drought index (KBDI) as an index for assessing fire danger potential. The index was gropued into three categories comprising low, moderate, and high fire danger levels.  Temporally, we found that fire danger level at the study area site are able to be grouped as follows: period of December to April was categorized low, period of July to October as high, and the remaining months as moderate. El Nino event had a severe influence on the severity and the duration of high KBDI that occurred until the end of November which normally a rainy season. Other finding is that there was a significant change (α=5%) on the rise of annual high KBDI frequency and average KBDI for period of 1984-2009, conversely frequency of rainy days decreased significantly. Information about when KBDI level reach high fire danger is of important for forest fire mangament in the region.